2021
DOI: 10.1111/bph.15429
|View full text |Cite
|
Sign up to set email alerts
|

Tectorigenin alleviates intrahepatic cholestasis by inhibiting hepatic inflammation and bile accumulation via activation of PPARγ

Abstract: Background and Purpose: Increasing evidence suggests that human cholestasis is closely associated with the accumulation and activation of hepatic macrophages.Research indicates that activation of PPARγ exerts liver protective effects in cholestatic liver disease (CLD), particularly by ameliorating inflammation and fibrosis, thus limiting disease progression. However, existing PPARγ agonists, such as troglitazone and rosiglitazone, have significant side effects that prevent their clinical application in the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 64 publications
(89 reference statements)
1
22
0
Order By: Relevance
“…However, in the liver of ANIT-induced CLD mouse models, FXR was increased by approximately 2-, 3.82-, and 2.41-fold after treatment with 25, 50, and 100 mpk PTE, respectively ( Figure 4B ). Previous studies found that macrophage-derived inflammatory factors (IL-1β, among others) activated NF-kB-p65 in hepatocytes, resulting in binding of NF-kB-p65 to the FXR promoter region, which precluded expression of FXR ( El Kasmi et al, 2018 ; Xiang et al, 2021 ). Consistent with this, when SIRT1 was absent from BMDMs, no significant change in expression of inflammatory factors ( Ccl2 , TNF-α , Ccr2 , and IL-1β ) was observed after PTE treatment of DDC-induced CLD model mice ( Figure 7G ); however, FXR protein levels in the liver were decreased ( Figure 7I ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the liver of ANIT-induced CLD mouse models, FXR was increased by approximately 2-, 3.82-, and 2.41-fold after treatment with 25, 50, and 100 mpk PTE, respectively ( Figure 4B ). Previous studies found that macrophage-derived inflammatory factors (IL-1β, among others) activated NF-kB-p65 in hepatocytes, resulting in binding of NF-kB-p65 to the FXR promoter region, which precluded expression of FXR ( El Kasmi et al, 2018 ; Xiang et al, 2021 ). Consistent with this, when SIRT1 was absent from BMDMs, no significant change in expression of inflammatory factors ( Ccl2 , TNF-α , Ccr2 , and IL-1β ) was observed after PTE treatment of DDC-induced CLD model mice ( Figure 7G ); however, FXR protein levels in the liver were decreased ( Figure 7I ).…”
Section: Discussionmentioning
confidence: 99%
“…Primary hepatocyte isolation was performed using a modified 2-step collagenase perfusion technique as previously reported ( Xiang et al, 2021 ). Briefly, the liver specimen was cannulated under sterile conditions and flushed once with 50 ml washing buffer containing 2.5 mM EGTA (SIGMA-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Xiang et al suggested that tectorigenin could treat DDC-induced cholestasis by increasing BSEP expression through PPARγ. Blocking upregulation of BSEP expression prevented the therapeutic effect of PPAR on cholestasis [ 48 ]. According to Zhang et al, Yin-Zhi-Huang could significantly decrease the serum total bile acids and DBLT levels, and improve histological disorganization by regulating Oatp2, Ntcp, and Mrp2 expression in cholestatic rats [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that the difference of PPARs distribution and affinity to agonist between hepatocytes and bile duct cells might provide an explanation. PPARα (Yang et al, 2019) and PPARγ (Xiang et al, 2021) have been reported to have protective effects in cholestasis by regulating bile acid metabolism in hepatocytes. In cholangiocytes, studies mainly focused on PPARγ, which played an important role in maintaining immune tolerance (Marra et al, 2005;Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%